2006
DOI: 10.1177/155005940603700316
|View full text |Cite
|
Sign up to set email alerts
|

EEG and the Variance of Motor Evoked Potential Amplitude

Abstract: The motor threshold is an important parameter in selecting the treatment intensity of patients undergoing transcranial magnetic stimulation. The large variance in magnitude of motor evoked responses has forced clinicians to perform many trials and average the results to find a repeatable value for motor threshold. Our objective is to investigate the source of the variance in amplitude. Four clinically healthy adult males participated in an EEG and EMG during transcranial magnetic stimulation of the left motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 20 publications
9
88
2
Order By: Relevance
“…The increase of corticospinal output induced by tACS at ␤ range is consistent among subjects, and it seems to be potent enough to overcome the poor relationships between amplitude/ phase of oscillatory 20 Hz spontaneous activity of rolandic neurons and the size of motor responses evoked by TMS of the motor cortex (Zarkowski et al, 2006;Mitchell et al, 2007;Lepage et al, 2008;Sauseng et al, 2009). A likely explanation is that spontaneous oscillations and MEPs size reflect the excitability of the human motor system in overlapping, but not identical, neuronal populations (Mäki and Ilmoniemi, 2010).…”
Section: Discussionmentioning
confidence: 84%
“…The increase of corticospinal output induced by tACS at ␤ range is consistent among subjects, and it seems to be potent enough to overcome the poor relationships between amplitude/ phase of oscillatory 20 Hz spontaneous activity of rolandic neurons and the size of motor responses evoked by TMS of the motor cortex (Zarkowski et al, 2006;Mitchell et al, 2007;Lepage et al, 2008;Sauseng et al, 2009). A likely explanation is that spontaneous oscillations and MEPs size reflect the excitability of the human motor system in overlapping, but not identical, neuronal populations (Mäki and Ilmoniemi, 2010).…”
Section: Discussionmentioning
confidence: 84%
“…At first glance this might seem somewhat surprising as previous studies found such associations. Zarkowski and colleagues [10], for example, found a strong relation between prestimulus alpha and gamma amplitudes and elicited MEP amplitude size. Similarly, Sauseng et al [9] report the strength of prestimulus alpha band amplitude predicting whether a TMS pulse would elicit an MEP or not, and Mäki and Ilmoniemi [14] found a strong correlation between MEP size and EEG beta amplitude.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that the magnitude of corticospinal excitability is determined by the amount of topographically specific alpha oscillations in the sensorimotor cortex. Additionally, Zarkowski and colleagues [10] were able to show that not only alpha band activity is a determinant of whether TMS elicits an MEP or not but also other frequency bands such as gamma. They found a highly significant relation between prestimulus gamma band activity and elicited MEP amplitude size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscular movements effect the EEG oscillations above 45 Hz. The high gamma band is shown to have the highest correlation with motor-evoked potentials (MEPs) [25]. A first-order band-pass Butterworth filter with a pass-band of 5-45 Hz is used to remove artefacts caused by biological movements.…”
Section: Preprocessingmentioning
confidence: 99%